Wayang Boneka Untuk Anak - Dewanto Sukistono (Institut Seni Indonesia Surakarta, 2008)
Planning of wayang boneka for children is supposed to be used as a developing media for behavior and basic ability shaping for play group children. This puppet can be extended personally as a game and in a group as a performance. It is defferent from other puppet performance. In wayang boneka performance, children act as the puppet, the dubber even the musician. The performance form can make them work cooperatively, self confidence, disciplined, responsible, and appraise each other.Keyword : wayang boneka, game, performance,play group children